Crosstalk Between Iron and Sulfur Homeostasis Networks in Arabidopsis - Khan, Muhammad Sayyar; Lu, Qiao; Cui, Man; Rajab, Hala; Wu, Huilan; Chai, Tuanyao; Ling, Hong-Qing (Frontiers in Plant Science, 2022)
The widespread deficiency of iron (Fe) and sulfur (S) is becoming a global concern. The underlying mechanisms regulating Fe and S sensing and signaling have not been well understood. We investigated the crosstalk between Fe and S using mutants impaired in Fe homeostasis, sulfate assimilation, and glutathione (GSH) biosynthesis. We showed that chlorosis symptoms induced by Fe deficiency were not directly related to the endogenous GSH levels. We found dynamic crosstalk between Fe and S networks and more interestingly observed that the upregulated expression of IRT1 and FRO2 under S deficiency in Col-0 was missing in the cad2-1 mutant background, which suggests that under S deficiency, the expression of IRT1 and FRO2 was directly or indirectly dependent on GSH. Interestingly, the bottleneck in sulfite reduction led to a constitutively higher IRT1 expression in the sir1-1 mutant. While the high-affinity sulfate transporter (Sultr1;2) was upregulated under Fe deficiency in the roots, the low-affinity sulfate transporters (Sultr2;1, and Sultr2;2) were down-regulated in the shoots of Col-0 seedlings. Moreover, the expression analysis of some of the key players in the Fe–S cluster assembly revealed that the expression of the so-called Fe donor in mitochondria (AtFH) and S mobilizer of group II cysteine desulfurase in plastids (AtNFS2) were upregulated under Fe deficiency in Col-0. Our qRT-PCR data and ChIP-qPCR experiments suggested that the expression of AtFH is likely under the transcriptional regulation of the central transcription factor FIT.